PENGARUH SOCIAL MEDIA MARKETING DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN PERUSAHAAN DIGITAL MANAA STUDIO - Ramagia Deskan; Rivera Pantro Sukma Silitonga (LPPM Universitas Asa Indonesia, 2023)
This research was conducted to determine the effect of social media marketing and price perceptions on consumer satisfaction through purchasing decisions at digital company Manaa Studio. The sample in this research is Manaa Studio customers who have been customers more than once. The sampling technique used purposive sampling of 150 samples. Methods of data collection using questionnaires distributed to respondents. While testing the hypothesis includes path analysis with the help of SmartPLS 3.2. The results found in Manaa Studio's research show that the influence of social media marketing and price perceptions influences consumer satisfaction through purchasing decisions, both directly and indirectly. For the social media marketing mediation variable, it has a significant effect on consumer satisfaction through purchasing decisions and price perceptions have a significant effect on consumer satisfaction through purchasing decisions. The coefficient of determination of purchasing decisions is 79.9% and consumer satisfaction is 47.8%.